Utilização dos computadores como ferramentas didáticas auxiliares para o aprendizado através da modelagem matemática baseada na Teoria Construtivista Piagetiniana. - Borges dos Santos, Ramon Oliveira; Moraes Rosa, Any; Moraes Rosa, Adriano Carlos (ECCOM: Educação, Cultura e Comunicação)
This work aims to contribute to early childhood education, using mathematical modeling and Information and Communication Technologies (ICTs) as active methodologies. Mathematical modeling allied with Piaget's constructivist theory are presented in this work as a tool aimed at helping teachers to transmit knowledge to students in a clear and efficient way and also with the preparation of classes. In relation to ICT's has been gaining more and more space in the educational scenario, technologies, technological devices and applications have become part of the students' daily lives. With this, applications can become valuable interaction tools to assist in teaching especially children. Through this conception, it proposes the use of the computer and educational applications, as a favorable tool for the teaching-learning process, in order to make the class more attractive and playful, aiming to improve students' performance in academic activities. With this, the student feels motivated and confident to understand the objective of their study, seeking resources that allow a greater benefit of the taught contents, thus developing their skills for a previous and constructive knowledge.